Pemberdayaan Peternak Sapi Perah melalui Pelatihan Pembuatan Produk Susu Varian Rasa di Pulung Ponorogo: Empowerment of Dairy Farmers Through Training on Making Flavored Dairy Products in Pulung Ponorogo - Rahmawati, Yunaita; Dwijayanto, Arik; Nugroho, Wisnu Aji (LP2M INSURI Ponorogo, 2022)
Wagir Kidul Village is located in Pulung District, Ponorogo Regency, where most of the population has a livelihood as farmers and dairy farmers. The productivity of cow's milk from dairy milking is in the range of 7 to 9 liters for one cow. The problem faced by farmers in Wagir Kidul Village is that they always follow the collectors where the selling price of cow's milk can change every day, sometimes it is priced erratically, which can be Rp. 6,000, - sometimes up to Rp. 10,000, - for each liter. The purpose of this service is to empower cattle farmers through training in making flavored milk products. The service method used is the Asset Based Community Development (ABCD) method. Products resulting from the manufacture of flavored milk variants have a better taste and higher economic value because they provide an alternative taste for buyers. The conclusion of this service is that the training carried out is able to increase the knowledge and creativity of cow breeders in processing ordinary fresh milk into milk variants that are economically feasible. Desa Wagir Kidul terletak di Kecamatan Pulung, Kabupaten Ponorogo. Sebagian besar penduduknya bekerja sebagai petani dan peternak sapi perah. Produktivitas perahan susu sapi sekitar tujuh hingga sembilan liter untuk satu ekor sapi pada setiap harinya. Masalah yang dihadapi peternak Desa Wagir Kidul adalah selalu mengikuti harga pengepul di mana harga jual susu sapi yang tidak stabil. Peternak hanya mendapat harga jual Rp6.000,00 atau Rp10.000,00 untuk setiap liternya. Tujuan pengabdian ini adalah pemberdayaan peternak sapi melalui pelatihan pembuatan produk susu dengan berbagai varian rasa. Metode pengabdian yang digunakan adalah metode Asset Based Community Development (ABCD). Produk hasil dari pembuatan susu varian rasa memiliki cita rasa lebih baik dan nilai ekonomi yang lebih tinggi karena menyediakan alternatif pilihan rasa bagi pembeli. Simpulan dari pengabdian ini adalah pelatihan yang dilaksanakan mampu menambah pengetahuan dan kreativitas peternak sapi dalam mengolah susu segar menjadi susu varian rasa yang bernilai ekonomi tinggi.